2022
DOI: 10.3390/ani12060682
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chemical Composition, Amino Acid Content, and Rumen Degradation Characteristics of Six Organic Feeds

Abstract: The current study was designed to investigate the chemical composition, amino acid content, and rumen degradation characteristics (nylon bag method) of six organic feeds to illustrate their feeding values. The feeds analyzed were: corn grain (CG), soybean cake (SC), wheat bran (WB), corn silage (CS), oat hay (OT), and alfalfa hay (AF). Our results showed that the contents of crude protein (CP) (47.46%) and ether extract (EE) (8.23%) in SC were highest. The contents of neutral detergent fiber (NDF) (65.00%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Individual and total AA profiles in wheat silage were similar among treatments. The total AAs profile averaged 60% of CP, which is in line with other findings [ 48 , 49 , 50 ]. The profiles of lysine and methionine relative to total EAA were lowest in urea and MI + urea, respectively, which might imply the extensive metabolism (e.g., hydrolysis or/and synthesis) of microbial communities in silages [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…Individual and total AA profiles in wheat silage were similar among treatments. The total AAs profile averaged 60% of CP, which is in line with other findings [ 48 , 49 , 50 ]. The profiles of lysine and methionine relative to total EAA were lowest in urea and MI + urea, respectively, which might imply the extensive metabolism (e.g., hydrolysis or/and synthesis) of microbial communities in silages [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…The formulation of dairy cow concentrate (KSA) in this study had a greater TNEAA content than the concentrate in the study by Zhao et al [25] , which was 8.97%–9.3% of DM (calculated NEAA and Arg). Luo et al [26] reported a range of 4.17%–23.22% for TNEAA content in grains. Moreover, Li et al [27] reported that the range of TNEE in plant-based and animal-source feedstuffs was 4.62–37.51 and 23.86%–81.99%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…DM degradation is an important index to measure the dry matter intake (DMI) of ruminants [ 25 ], which reflects the overall degradation effect of roughage in the rumen [ 26 ]. In this experiment, the effective degradation rates of DM in GS (42.53%) was significantly higher than that of AS (37.12%), and the DM degradation rate of GS at 72 h was 57.51%, which was significantly higher than that of AS (51.85%), indicating that GS was more easily decomposed and utilized by the body during digestion [ 27 ], resulting in a higher utilization rate in the rumen.…”
Section: Discussionmentioning
confidence: 99%